The effects of severe periodontitis on arterial stiffness using cardio‐ankle vascular index in patients with type 2 diabetes - Torumtay Cin, Gizem; Fenkci, Semin Melahat; Kiliç, Ismail Doğu; Aslan, Halil Serdar; Sevgican, Cihan İlyas; Şenol, Hande (Journal of periodontal research, 2024)
Background and Objective Arterial stiffness, which is a measure of the elasticity of the arteries, is also a risk factor for the development of cardiovascular diseases and its measurement is important for evaluating the atherosclerosis process. The purpose of this cross‐sectional study to investigate whether severe periodontitis in short‐term type 2 diabetes may be associated with increased cardio‐ankle vascular index (CAVI) values specified for subclinical atherosclerosis risk. Methods A total of 136 subjects, including 69 subjects with short‐term type 2 diabetes (35 with severe periodontitis and 34 with periodontally healthy) and 67 systemically healthy subjects (32 with severe periodontitis and 35 with periodontally healthy) were enrolled to this study. Assessment of all participants included in this study in terms of arterial stiffness was determined by CAVI. Serum fasting plasma glucose (FPG), glycated haemoglobin (HbA1c), triglyceride (TRG), high‐density lipoprotein (HDL), low‐density lipoprotein (LDL), total cholesterol (TC) and C‐reactive protein (CRP) levels were calculated using standard methods. Full mouth periodontal measurements were recorded. Multiple linear regression analysis was performed to evaluate the relationship between periodontal parameters and mean CAVI values of the groups. Results Mean CAVI levels were significantly higher in diabetic and periodontitis group compared to the other study groups (p < .05). In diabetes and periodontitis group, CAVI was showed positive correlations with CRP (r = .337, p = .048) and HbA1c (r = .442, p = .008). Also, positive significant correlations were found with probing depth (PD) and clinical attachment level (CAL) in the periodontitis groups. Multiple regression analysis revealed that CAL independently predicted CAVI levels in periodontitis groups (β = .433, p = .019 in diabetes and periodontitis groups and β = .57, p = .001 in systemically healthy and periodontitis group respectively). Conclusion This is the first study investigating the association between severe periodontitis and CAVI in patients with short‐term diabetes. Our findings suggest that severe periodontitis may be an intermediate factor in the pathway between type 2 diabetes and cardiovascular disease by increasing the arterial stiffness.